Tamura Hachidayū and the "Masters of Sacred Dance" - Groemer, Gerald (Japanese journal of religious studies, 2011)
During the Edo period (1600-1868) many genres of kagura and related arts were performed at shrines and temples in eastern Japan by men under the direction of Tamura Hachidayū, whose position and name was hereditary. Tamura served as the head priest of the Sanja Gongen, the tutelary shrine of Sensōji. Although Tamura maintained that his lineage and rights of control over sacred dancers dated to the medieval period and was indisputable, a closer look at relevant documents reveals that his rise to an elevated position in the Edo-period religious hierarchy took place against a backdrop of political machinations and legal altercations. This article explores the rise and fall of Tamura and his organization and seeks to contextualize the vicissitudes of his organization in the broader political history of the Edo and Meiji periods.